2013
DOI: 10.1007/s12298-013-0167-5
|View full text |Cite
|
Sign up to set email alerts
|

Copper-stress induced alterations in protein profile and antioxidant enzymes activities in the in vitro grown Withania somnifera L.

Abstract: Withania somnifera L. seedlings were grown in half-strength MS (Murashige and Skoog) basal medium for 4 weeks and then transferred to full-strength MS liquid medium for 3 weeks. The sustainable plants were subcultured in the same medium but with different concentrations (0, 25, 50, 100 and 200 μM) of Cu for 7 and 14 days. The growth parameters (root length, shoot length, leaf length and total number of leaves per plant) showed a declining trend in the treated plants in a concentration dependant manner. Roots a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Proteomic responses to Cu stress linked to Cu tolerance have previously been observed in other organisms. Cu exposure experiments in plants and fungi have observed increases in soluble protein that has been linked to induction of anti-oxidant enzymes (Cavalcanti Luna et al, 2015;Gao et al, 2008;Rout et al, 2013) while induction of Cu-binding proteins has been demonstrated in a Cu-tolerant variety of rice (Chen et al, 2015). Mechanisms of Cu tolerance in algae are not well understood, and may involve differential Cu uptake and internalisation in some cases (Levy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic responses to Cu stress linked to Cu tolerance have previously been observed in other organisms. Cu exposure experiments in plants and fungi have observed increases in soluble protein that has been linked to induction of anti-oxidant enzymes (Cavalcanti Luna et al, 2015;Gao et al, 2008;Rout et al, 2013) while induction of Cu-binding proteins has been demonstrated in a Cu-tolerant variety of rice (Chen et al, 2015). Mechanisms of Cu tolerance in algae are not well understood, and may involve differential Cu uptake and internalisation in some cases (Levy et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(Table 2). Some of these Cu-enzymes are cytochrome oxidase, Cu/Zn-superoxide dismutase (Cu/ ZnSOD), laccase, ascorbate oxidase, amino oxidase, polyphenol oxidase and plastocyanin (Yruela 2005;Ravet et al 2011;Rout et al 2013). Plastocyanin, being the most abundant copper protein promotes electron transport in the thylakoid lumen of chloroplasts (Yruela 2005; Abdel- (2000), Dear and Weir (2004) Boron-toxicity Above 0.3-1 ppm and 3-100 lg g -1 dry weight Higher concentration of boron in plants would lead to Yellowing of the leaf tips and distorted shoot growth Chlorotic and necrotic patches in the margin/ older leaves spots on fruits Nable et al (1997), Stangoulis and Reid (2002), Reid et al (2004), Nable et al (1997) DW Improper growth rate and distortion or whitening (chlorosis) of young leaves Decrease in cell wall formation lignification in several tissues and curling of leaf margins Damages apical meristem, fruit formation, pollen development, the fruit and seed production, wood production Inhibits embryo development, seed viability and plant development Marschner (1995), Epstein and Bloom (2005), Ruiter (1969), Küpper et al (2003), Yruela (2005), Burkhead et al (2009a, b) Toxicity of Cu Above 20 lg g -1 DW or higher Chlorosis and necrosis, stunting, and inhibition of root and shoot growth Inhibit enzyme activity and protein function, which later produces highly toxic hydroxyl radicals leading to oxidative damage of plant cell Gratão et al (2005), Vinit-Dunand et al (2002), Küpper et al (2003), Yruela et al (2009) Ghany and Pilon 2008).…”
Section: Copper (Cu)mentioning
confidence: 99%
“…Xác định hàm lượng Cu trong huyết tương và gan gà Để xác định nguyên nhân chính khiến gà chậm tăng cân hơn so với bình thường, chúng tôi đã tiến hành đo hàm lượng Cu có trong huyết tương gà bằng phương pháp ICP-MS. Các nghiên cứu trước đây đã chỉ ra sự tích lũy Cu vượt mức cho phép trong các cơ quan của cơ thể có ảnh hưởng đến quá trình sinh lý của động vật và là nguyên nhân dẫn đến một số căn bệnh nguy hiểm (Galhardi et al, 2004;Rout et al, 2013). Hiện nay, một số công bố cho thấy khi tăng nhẹ nồng độ Cu trong thức ăn có thể làm giảm nồng độ cholesterol và triglyceride trong máu của gà (Rahman et al, 2001;Skrivanova, 2004), nhưng hàm lượng nano Cu trong huyết tương tăng có thể làm tăng nồng độ calcium (Ca), phosphorus (P) và sắt (Fe) có trong gà thịt (Mroczek-Sosnowska et al, 2013).…”
Section: đáNh Giá Tỷ Lệ Nuôi Sống Và Sự Thay đổI Thể Trọng Của Gàunclassified